Carbon dioxide hydrogenation catalyst as well as preparation method and application thereof

By loading Mo2C on the outer surface of CeO2 nanorod support, the Mo2C/CeO2 catalyst is formed, which solves the problem of low ethanol selectivity of the existing catalyst and achieves efficient ethanol preparation.

CN119608196AActive Publication Date: 2025-03-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411503898.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-03-14
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing catalysts used for CO2 hydrogenation to produce ethanol have low selectivity and are difficult to meet the needs of efficient preparation of ethanol.

Method used

The catalyst Mo2C/CeO2 with a nanorod support structure is used to support the active component Mo2C on the outer surface of the CeO2 nanorod support to form a synergistic catalytic reaction layer to improve the ethanol selectivity of the catalyst.

Benefits of technology

The ethanol selectivity of the carbon dioxide hydrogenation catalyst during the reaction process is significantly improved, and the catalytic activity and ethanol selectivity are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608196A_ABST
    Figure CN119608196A_ABST
Patent Text Reader

Abstract

The invention provides a carbon dioxide hydrogenation catalyst and a preparation method and application thereof, and relates to the technical field of catalyst preparation. The catalyst comprises a carrier and an active component, the carrier is of a nanorod structure, the active component Mo2C is loaded on the outer surface of the carrier, a catalytic reaction layer is formed by the active component Mo2C and the outer surface of the carrier, cooperative regulation is carried out, and the ethanol selectivity of the catalyst is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a carbon dioxide hydrogenation catalyst and a preparation method and application thereof. Background Art

[0002] Due to industrial and human activities, CO2 emissions from fossil fuel combustion have been rising year by year, causing global climate change and gradually attracting people's attention. CO2 is an abundant, sustainable and renewable carbon resource. The use of CO2 can not only reduce CO2 emissions, but also convert CO2 into valuable chemical products or energy. Therefore, the use of CO2 has important strategic significance.

[0003] At present, CO2 hydrogenation is mostly used to synthesize methanol, such as Chinese patents CN111530458A, CN106861689A, etc. Compared with synthesizing methanol, synthesizing low-toxic ethanol is a better choice. Ethanol is not only an important basic chemical raw material, but also an excellent liquid fuel and gasoline additive. It has a simpler transportation process and better stability.

[0004] Therefore, the technology of using green hydrogen to catalytically hydrogenate CO2 to produce ethanol has attracted widespread attention, but the ethanol selectivity of the catalyst currently used for direct hydrogenation of CO2 / CO to produce ethanol is still not ideal. Chinese patent CN111185209A discloses a preparation of a molybdenum carbide-supported nickel-based catalyst and its application in the hydrogenation of carbon dioxide to produce ethanol. The technology uses NiMoO x As a precursor, Ni / Mo2C catalyst was prepared by carbonization for ethanol synthesis, but the ethanol selectivity was low.

[0005] In summary, the development of a hydrogenation catalyst with high ethanol selectivity has very important application significance. Summary of the invention

[0006] In view of the low ethanol selectivity of current CO2 hydrogenation catalysts to ethanol, the present invention provides a catalyst Mo2C / CeO2 with a nanorod carrier structure to improve the ethanol selectivity of the carbon dioxide hydrogenation catalyst during the reaction process.

[0007] One of the objectives of the present invention is to provide a carbon dioxide hydrogenation catalyst.

[0008] A second object of the present invention is to provide a method for preparing the carbon dioxide hydrogenation catalyst.

[0009] The third object of the present invention is to provide an application of the carbon dioxide hydrogenation catalyst.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0011] In a first aspect, the present invention provides a carbon dioxide hydrogenation catalyst, comprising a CeO2 nanorod carrier, and an active component Mo2C loaded on the outer surface of the carrier;

[0012] Based on the mass of CeO2 nanorod support, the loading amount of active component Mo2C is 3.5wt%-30.5wt%.

[0013] In some embodiments, the diameter of the CeO2 nanorod support is 8-12 nm.

[0014] The catalyst of the invention comprises a carrier and an active component. The carrier has a nanorod structure. The active component Mo2C is loaded on the outer surface of the carrier and forms a catalytic reaction layer with the outer surface of the carrier for coordinated regulation.

[0015] In a second aspect, the present invention provides a method for preparing the above-mentioned carbon dioxide hydrogenation catalyst, comprising the following steps:

[0016] S1, providing a CeO2 nanorod carrier;

[0017] S2, loading a molybdenum salt onto a CeO2 nanorod carrier, and then drying in air to obtain MoO3 / CeO2, wherein the loading amount of MoO3 is 5wt%-30wt% based on the total mass of CeO2 and MoO3;

[0018] S3. Reducing and carbonizing MoO3 / CeO2 at elevated temperatures to obtain a carbon dioxide hydrogenation catalyst Mo2C / CeO2.

[0019] Step S1:

[0020] In some embodiments, the method for preparing the CeO2 nanorod carrier comprises the following steps:

[0021] The cerium salt is dissolved in deionized water and magnetically stirred to form a cerium precursor aqueous solution; a strong alkali aqueous solution is dropped into the cerium precursor aqueous solution for precipitation to obtain a mixed suspension; the mixed suspension is placed in a polytetrafluoroethylene kettle with a stainless steel high-pressure sterilizer for hydrothermal treatment; the precipitate is collected, separated, washed with deionized water and ethanol for several times, and then dried in a vacuum oven; the dried powder is calcined in air to obtain a CeO2 nanorod carrier.

[0022] Preferably, the cerium salt is at least one selected from Ce(NO3)3·6H2O, (CH3CO2)3Ce·6H2O and CeCl3·7H2O;

[0023] Preferably, the mass volume concentration of the cerium precursor aqueous solution is 0.2 to 0.5 g / ml;

[0024] Preferably, the strong alkali aqueous solution is at least one selected from a NaOH aqueous solution and a KOH aqueous solution;

[0025] Preferably, the molar concentration of the strong alkali aqueous solution is 10 to 20 mol / L;

[0026] Preferably, the volume ratio of the cerium precursor aqueous solution to the strong alkali aqueous solution is 1:4-6;

[0027] Preferably, the hydrothermal treatment temperature is 100-150°C and the time is 5-24h;

[0028] Preferably, the calcination temperature is 300-600° C. and the calcination time is 1-4 hours.

[0029] Step S2:

[0030] Molybdenum salt can be loaded on CeO2 nanorod carrier by impregnation method, sol-gel method, etc.

[0031] In some embodiments, the molybdenum salt is at least one selected from molybdic acid, paramolybdic acid, molybdate and paramolybdate, preferably ammonium molybdate.

[0032] Method 1, sol-gel method: dissolve molybdenum salt in deionized water to form a molybdenum salt aqueous solution, add citric acid, and cook in a water bath to make it sol-like, and then place the CeO2 nanorod carrier in the sol. Based on the total mass of the CeO2 nanorod carrier and MoO3, the loading amount of MoO3 is 5wt%-30wt%.

[0033] Preferably, citric acid and Mo 3+ The amount of substance ratio is 1-1.1:1;

[0034] Preferably, the water bath temperature is 60-100°C, preferably 80°C.

[0035] Method 2, impregnation method: dissolve molybdenum salt in deionized water to form a molybdenum salt aqueous solution, place the CeO2 nanorod carrier into the molybdenum salt aqueous solution for equal volume impregnation, based on the total mass of the CeO2 nanorod carrier and MoO3, the loading amount of MoO3 is 5wt%-30wt%.

[0036] Step S3:

[0037] In some embodiments, the reduction comprises: introducing hydrogen and raising the temperature to 300-400° C.;

[0038] In some embodiments, the temperature-raising carbonization comprises: introducing a carbonizing gas, raising the temperature to 700-800° C. at a heating rate of 2-5° C. / min and maintaining the temperature for 2-4 hours;

[0039] Preferably, the carbonization gas comprises methane and hydrogen, with the volume content of methane being 10-20% and the volume content of hydrogen being 80-90%.

[0040] In a third aspect, the present invention provides a use of the above-mentioned carbon dioxide hydrogenation catalyst in preparing ethanol by hydrogenation of carbon dioxide.

[0041] Preferably, the reaction conditions of the carbon dioxide hydrogenation catalyst are: reaction temperature of 200-400°C, reaction pressure of 2-8 MPa, volume space velocity of 2000-6000 h -1 , the volume ratio of hydrogen to carbon dioxide is 4:1 to 1:1.

[0042] Technical effects:

[0043] The carbon dioxide hydrogenation catalyst created by the present invention has a special CeO2 nanorod structure with a diameter of 8-12nm. The active component Mo2C is loaded on the outer surface of the carrier and forms a catalytic reaction layer with the outer surface of the carrier. MoO3 / CeO2 produces a strong synergistic effect, and the H2 reduction peaks of CeO2 nanorods and MoO3 appear between 585°C and 590°C. After the Mo2C / CeO2 carbon dioxide hydrogenation catalyst is carbonized, the CO2 activated by CeO2 and the H2 activated by molybdenum carbide react synergistically, thereby improving the catalyst's ethanol selectivity.

[0044] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is the H2-TPR spectrum of the MoO3 / CeO2 catalyst prepared in Example 1. DETAILED DESCRIPTION

[0046] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.

[0047] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.

[0048] Example 1

[0049] (1) Dissolve 26.4 g Ce(NO3)3·6H2O in 100 ml deionized water and stir with a magnetic stirrer to form a cerium precursor solution A. Dissolve 252.0 g NaOH in 400 ml deionized water to form a solution B, and drop the solution B into the A solution.

[0050] (2) The mixture of A and B was placed in a polytetrafluoroethylene autoclave with a stainless steel autoclave and subjected to hydrothermal treatment at 100°C for 24 h. After the hydrothermal treatment, the precipitate was separated, washed several times with deionized water and ethanol, and then dried in a vacuum oven at 60°C for 12 h. The dried powder was calcined in a muffle furnace at 500°C for 2 h to form a CeO2 nanorod carrier.

[0051] (3) 1.22 g (NH4)6Mo7O 24 ·4H2O was dissolved in 10ml of deionized water, 1.4g of citric acid was added, 9g of CeO2 nanorods prepared in (2) were added, and the mixture was stirred at 80°C to load the molybdenum salt solution on the CeO2 nanorod carrier. The prepared precursor was dried in an oven. The loading amount of MoO3 relative to MoO3 / CeO2 was 10wt%, and the loading amount of MoO3 relative to CeO2 was 11.1wt%.

[0052] (4) After drying, the catalyst was reduced in the reaction tube and carbonized by heating. Hydrogen was introduced into the device and the temperature was raised to 300°C. Starting from 300°C, carbonizing gas (methane content 10%, hydrogen content 90%) was introduced and the temperature was raised to 700°C at a heating rate of 2°C / min and maintained for 3 hours to complete carbonization and prepare Mo2C / CeO2. The loading amount of Mo2C relative to CeO2 was 7.86wt%. Its H2-TPR spectrum is shown as follows: Figure 1 As shown, MoO3 / CeO2 produces a strong synergistic effect and the H2 reduction peaks of CeO2 nanorods and MoO3 appear between 585℃ and 590℃.

[0053] Example 2

[0054] (1) Dissolve 26.4 g Ce(NO3)3·6H2O in 100 ml deionized water and stir with a magnetic stirrer to form a cerium precursor solution A. Dissolve 252.0 g NaOH in 400 ml deionized water to form a solution B, and drop the solution B into the A solution.

[0055] (2) The mixture of A and B was placed in a polytetrafluoroethylene autoclave with a stainless steel autoclave and subjected to hydrothermal treatment at 100°C for 24 h. After the hydrothermal treatment, the precipitate was separated, washed several times with deionized water and ethanol, and then dried in a vacuum oven at 60°C for 12 h. The dried powder was calcined in a muffle furnace at 500°C for 2 h to form a CeO2 nanorod carrier.

[0056] (3) 2.44 g (NH4)6Mo7O 244H2O was dissolved in 4 ml of deionized water, and 8 g of CeO2 nanorods prepared in (2) were added and loaded on the CeO2 nanorod carrier by impregnation. The prepared precursor was dried in stagnant air. The loading amount of MoO3 relative to MoO3 / CeO2 was 20 wt%, and the loading amount of MoO3 relative to CeO2 was 25 wt%.

[0057] (4) After drying, the catalyst was reduced in a reaction tube and carbonized by heating. Hydrogen was introduced into the device and the temperature was raised to 300°C. Starting from 300°C, carbonizing gas (methane content 10%, hydrogen content 90%) was introduced and the temperature was raised to 700°C at a heating rate of 2°C / min and maintained for 3 hours to complete carbonization and prepare Mo2C / CeO2. The loading amount of Mo2C relative to CeO2 was 17.7wt%.

[0058] Example 3

[0059] (1) Dissolve 26.4 g Ce(NO3)3·6H2O in 100 ml deionized water and stir with a magnetic stirrer to form a cerium precursor solution A. Dissolve 252.0 g NaOH in 400 ml deionized water to form a solution B, and drop the solution B into the A solution.

[0060] (2) The mixture of A and B was placed in a polytetrafluoroethylene autoclave with a stainless steel autoclave and subjected to hydrothermal treatment at 100°C for 24 h. After the hydrothermal treatment, the precipitate was separated, washed several times with deionized water and ethanol, and then dried in a vacuum oven at 60°C for 12 h. The dried powder was calcined in a muffle furnace at 500°C for 2 h to form a CeO2 nanorod carrier.

[0061] (3) 0.61 g (NH4)6Mo7O 24 4H2O was dissolved in 4 ml of deionized water, and 9.5 g of CeO2 nanorods prepared in (2) were added and loaded on the CeO2 nanorod carrier by impregnation. The prepared precursor was dried in stagnant air. The loading amount of MoO3 relative to MoO3 / CeO2 was 5 wt%, and the loading amount of MoO3 relative to CeO2 was 5.26 wt%.

[0062] (4) After drying, the catalyst was reduced in a reaction tube and carbonized by heating. Hydrogen was introduced into the device and the temperature was raised to 300°C. Starting from 300°C, carbonizing gas (methane content 10%, hydrogen content 90%) was introduced and the temperature was raised to 700°C at a heating rate of 2°C / min and maintained for 3 hours to complete carbonization and prepare Mo2C / CeO2. The loading amount of Mo2C relative to CeO2 was 3.72wt%.

[0063] Example 4

[0064] (1) Dissolve 26.4 g Ce(NO3)3·6H2O in 100 ml deionized water and stir with a magnetic stirrer to form a cerium precursor solution A. Dissolve 252.0 g NaOH in 400 ml deionized water to form a solution B, and drop the solution B into the A solution.

[0065] (2) The mixture of A and B was placed in a polytetrafluoroethylene autoclave with a stainless steel autoclave and subjected to hydrothermal treatment at 100°C for 24 h. After the hydrothermal treatment, the precipitate was separated, washed several times with deionized water and ethanol, and then dried in a vacuum oven at 60°C for 12 h. The dried powder was calcined in a muffle furnace at 500°C for 2 h to form a CeO2 nanorod carrier.

[0066] (3) 1.22 g (NH4)6Mo7O 24 4H2O was dissolved in 4 ml of deionized water, and 9 g of CeO2 nanorods prepared in (2) were added and loaded on the CeO2 nanorod carrier by impregnation. The prepared precursor was dried in stagnant air. The loading amount of MoO3 relative to MoO3 / CeO2 was 10 wt%, and the loading amount of MoO3 relative to CeO2 was 11.1 wt%.

[0067] (4) After drying, the catalyst was reduced in a reaction tube and carbonized by heating. Hydrogen was introduced into the device and the temperature was raised to 300°C. Starting from 300°C, carbonizing gas (methane content 10%, hydrogen content 90%) was introduced and the temperature was raised to 700°C at a heating rate of 2°C / min and maintained for 3 hours to complete carbonization and prepare Mo2C / CeO2. The loading amount of Mo2C relative to CeO2 was 7.86wt%.

[0068] Example 5

[0069] (1) Dissolve 26.4 g Ce(NO3)3·6H2O in 100 ml deionized water and stir with a magnetic stirrer to form a cerium precursor solution A. Dissolve 252.0 g NaOH in 400 ml deionized water to form a solution B, and drop the solution B into the A solution.

[0070] (2) The mixture of A and B was placed in a polytetrafluoroethylene autoclave with a stainless steel autoclave and subjected to hydrothermal treatment at 100°C for 24 h. After the hydrothermal treatment, the precipitate was separated, washed several times with deionized water and ethanol, and then dried in a vacuum oven at 60°C for 12 h. The dried powder was calcined in a muffle furnace at 500°C for 2 h to form a CeO2 nanorod carrier.

[0071] (3) 3.66 g (NH4)6Mo7O 244H2O was dissolved in 10 ml of deionized water, 4 g of citric acid was added, and 7 g of CeO2 nanorods prepared in (2) were added, and stirred at 80°C to load the molybdenum salt solution on the CeO2 nanorod carrier. The prepared precursor was dried in an oven. The loading amount of MoO3 relative to MoO3 / CeO2 was 30 wt%, and the loading amount of MoO3 relative to CeO2 was 42.8 wt%.

[0072] (4) After drying, the catalyst was reduced in a reaction tube and carbonized by heating. Hydrogen was introduced into the device and the temperature was raised to 300°C. Starting from 300°C, carbonizing gas (methane content 10%, hydrogen content 90%) was introduced and the temperature was raised to 700°C at a heating rate of 2°C / min and maintained for 3 hours to complete carbonization and prepare Mo2C / CeO2. The loading amount of Mo2C relative to CeO2 was 30.34wt%.

[0073] Comparative Example 1

[0074] (1) Dissolve 26.4 g Ce(NO3)3·6H2O in 100 ml deionized water and stir with a magnetic stirrer to form a cerium precursor solution A. Dissolve 252.0 g NaOH in 400 ml deionized water to form a solution B, and drop the solution B into the A solution.

[0075] (2) The mixture of A and B was placed in a polytetrafluoroethylene autoclave with a stainless steel autoclave and subjected to hydrothermal treatment at 100°C for 24 h. After the hydrothermal treatment, the precipitate was separated, washed several times with deionized water and ethanol, and then dried in a vacuum oven at 60°C for 12 h. The dried powder was calcined in a muffle furnace at 500°C for 2 h to form a CeO2 nanorod carrier.

[0076] (3) 4.88 g (NH4)6Mo7O 24 4H2O was dissolved in 10 ml of deionized water, 5.3 g of citric acid was added, and 6 g of CeO2 nanorods prepared in (2) were added, and stirred at 80°C to load the molybdenum salt solution on the CeO2 nanorod carrier. The prepared precursor was dried in an oven. The loading amount of MoO3 relative to MoO3 / CeO2 was 40 wt%, and the loading amount of MoO3 relative to CeO2 was 66.7 wt%.

[0077] (4) After drying, the catalyst was reduced in a reaction tube and carbonized by heating. Hydrogen was introduced into the device and the temperature was raised to 300°C. Starting from 300°C, carbonizing gas (methane content 10%, hydrogen content 90%) was introduced and the temperature was raised to 700°C at a heating rate of 2°C / min and maintained for 3 hours to complete carbonization and prepare Mo2C / CeO2. The loading amount of Mo2C relative to CeO2 was 47.2wt%.

[0078] Comparative Example 2

[0079] (1) Dissolve 26.4 g Ce(NO3)3·6H2O in 100 ml deionized water and stir with a magnetic stirrer to form a cerium precursor solution A. Dissolve 252.0 g NaOH in 400 ml deionized water to form a solution B, and drop the solution B into the A solution.

[0080] (2) The mixture of A and B was placed in a polytetrafluoroethylene autoclave with a stainless steel autoclave and subjected to hydrothermal treatment at 100°C for 24 h. After the hydrothermal treatment, the precipitate was separated, washed several times with deionized water and ethanol, and then dried in a vacuum oven at 60°C for 12 h. The dried powder was calcined in a muffle furnace at 500°C for 2 h to form a CeO2 nanorod carrier.

[0081] (3) 1.22 g (NH4)6Mo7O 24 4H2O was dissolved in 4 ml of deionized water, and 9 g of CeO2 nanorods prepared in (2) were added and loaded on the CeO2 carrier by impregnation. The prepared precursor was dried in stagnant air. The loading amount of MoO3 relative to MoO3 / CeO2 was 10 wt%, and the loading amount of MoO3 relative to CeO2 was 11.1 wt%.

[0082] (4) Calcination in a muffle furnace at a heating rate of 2°C / min to 700°C and maintaining for 3 hours to obtain MoO3 / CeO2.

[0083] Comparative Example 3

[0084] (1) 26.4 g of Ce(NO3)3·6H2O was calcined at 500°C in a muffle furnace for 2 h to form a CeO2 carrier.

[0085] (2) 1.22 g (NH4)6Mo7O 24 4H2O was dissolved in 4 ml of deionized water, and 9 g of CeO2 prepared in (1) was added and loaded on the CeO2 carrier by impregnation. The prepared precursor was dried in an oven. The loading amount of MoO3 relative to MoO3 / CeO2 was 10 wt%, and the loading amount of MoO3 relative to CeO2 was 11.1 wt%.

[0086] (3) After drying, the catalyst was reduced in a reaction tube and carbonized by heating. Hydrogen was introduced into the device and the temperature was raised to 300°C. Starting from 300°C, carbonizing gas (methane content 10%, hydrogen content 90%) was introduced and the temperature was raised to 700°C at a heating rate of 2°C / min and maintained for 3 hours to complete carbonization and prepare Mo2C / CeO2. The loading amount of Mo2C relative to CeO2 was 7.86wt%.

[0087] Catalyst activity test:

[0088] The catalyst was loaded into the reactor, and the raw material gas was introduced. After the temperature was raised to the test conditions, the conditions were maintained stable for 30 minutes. The chromatographic injection began, and the sample analysis time was 30 minutes. The injection was repeated 3 times, and the average value of the 3 data was taken.

[0089] Test conditions: catalyst loading 1 mL, temperature: 230°C, pressure: 3.0 MPa, volume space velocity 3000 h -1 , H2:CO2 volume ratio = 3:1, the results are shown in Table 1.

[0090] CO2 conversion rate = (CO2 volume content before reaction - CO2 volume content after reaction) / (CO2 volume content before reaction) × 100%;

[0091] Ethanol selectivity = C2H6O volume content after reaction / (CO volume content after reaction + C i H x Volume content + C after reaction i H x O y Volume content) × 100%, where C i H x , C i H x O y Represent the volume contents of hydrocarbon and alcohol products respectively.

[0092] Table 1 Catalytic activity evaluation results of the finished catalysts of the examples and comparative examples

[0093]

[0094]

[0095] As can be seen from Table 1, when preparing MoO3 / CeO2 nanorod catalysts, or when the loading of MoO3 is too high, or when the carrier is not CeO2 nanorod catalyst, the conversion rate of carbon dioxide and the selectivity of ethanol are both low. The catalyst of the present invention exhibits good catalytic performance in the catalytic carbon dioxide hydrogenation reaction to produce ethanol, and the catalytic activity and the selectivity of ethanol have been significantly improved.

[0096] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.

Claims

1. A carbon dioxide hydrogenation catalyst, characterized in that It includes a CeO2 nanorod carrier and an active component Mo2C loaded on the outer surface of the carrier; Based on the mass of CeO2 nanorod support, the loading amount of active component Mo2C is 3.5wt%-30.5wt%.

2. The carbon dioxide hydrogenation catalyst according to claim 1, characterized in that The diameter of CeO2 nanorod carrier is 8-12nm.

3. A method for preparing a carbon dioxide hydrogenation catalyst according to claim 1 or 2, characterized in that: The following steps are involved: S1, providing a CeO2 nanorod carrier; S2, loading a molybdenum salt onto a CeO2 nanorod carrier, and then drying in air to obtain MoO3 / CeO2, wherein the loading amount of MoO3 is 5wt%-30wt% based on the total mass of CeO2 and MoO3; S3. Reducing and carbonizing MoO3 / CeO2 at elevated temperature to obtain Mo2C / CeO2 carbon dioxide hydrogenation catalyst.

4. The preparation method according to claim 3, characterized in that: The preparation method of the CeO2 nanorod carrier in step S1 comprises the following steps: The cerium salt is dissolved in deionized water and magnetically stirred to form a cerium precursor aqueous solution; a strong alkali aqueous solution is dropped into the cerium precursor aqueous solution for precipitation to obtain a mixed suspension; the mixed suspension is placed in a polytetrafluoroethylene kettle with a stainless steel high-pressure sterilizer for hydrothermal treatment; the precipitate is collected, separated, washed with deionized water and ethanol for several times, and then dried in a vacuum oven; the dried powder is calcined in air to obtain a CeO2 nanorod carrier.

5. The preparation method according to claim 4, characterized in that: The mass volume concentration of the cerium precursor aqueous solution is 0.2-0.5 g / ml; the molar concentration of the strong alkali aqueous solution is 10-20 mol / L; the volume ratio of the cerium precursor aqueous solution to the strong alkali aqueous solution is 1:4-6; The hydrothermal treatment temperature is 100-150°C and the time is 5-24h; The calcination temperature is 300-600°C and the time is 1-4 hours.

6. The preparation method according to claim 3, characterized in that: The loading of step S2 includes one of the following methods: Method 1: Dissolve molybdenum salt in deionized water to form a molybdenum salt aqueous solution, add citric acid, and cook in a water bath to make it present a sol state, and then place the CeO2 nanorod carrier in the sol; Method 2: The molybdenum salt is dissolved in deionized water to form a molybdenum salt aqueous solution, and the CeO2 nanorod carrier is placed in the molybdenum salt aqueous solution for equal volume impregnation.

7. The preparation method according to claim 3, characterized in that: In step S3, the reduction comprises: introducing hydrogen and raising the temperature to 300-400°C; The heating carbonization includes: introducing carbonization gas, heating to 700-800°C at a heating rate of 2-5°C / min and maintaining for 2-4h; The carbonized gas includes methane and hydrogen, with the volume content of methane being 10-20% and the volume content of hydrogen being 80-90%.

8. Use of the carbon dioxide hydrogenation catalyst according to claim 1 or 2 or the carbon dioxide hydrogenation catalyst prepared by the preparation method according to any one of claims 3 to 7 in preparing ethanol by hydrogenating carbon dioxide.

9. The use according to claim 8, characterized in that: The reaction conditions of the carbon dioxide hydrogenation catalyst include: a reaction temperature of 200 to 400° C., a reaction pressure of 2 to 8 MPa, and a volume space velocity of 2000 to 6000 h -1 , the volume ratio of hydrogen to carbon dioxide is 4:1 to 1:1.

Citation Information

Patent Citations

  • Ester hydrogenation catalyst and preparation method and application thereof

    CN106215943A

  • Molybdenum carbide / cerium oxide catalyst for ammonia synthesis and preparation method thereof

    CN110652991A

  • Preparation and application of catalyst for preparing methanol through carbon dioxide hydrogenation

    CN110787789A

  • Preparation of molybdenum carbide supported nickel-based catalyst, and application of molybdenum carbide supported nickel-based catalyst in ethanol preparation through carbon dioxide hydrogenation

    CN111185209A

  • Co-CeO2 catalyst for preparing low-carbon alcohol from synthesis gas and preparation method and application

    CN113952960A